2020
DOI: 10.1177/1729881420910530
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal voxel layer: A view on robot perception for the dynamic world

Abstract: The spatio-temporal voxel grid is an actively maintained open-source project providing an improved three-dimensional environmental representation that has been garnering increased adoption in large, dynamic, and complex environments. We provide a voxel grid and the Costmap 2-D layer plug-in, Spatio-Temporal Voxel Layer, powered by a real-time sparse occupancy grid with constant time access to voxels which does not scale with the environment’s size. We replace ray-casting with a new clearing technique we dub fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 29 publications
0
13
0
7
Order By: Relevance
“…To implement our system, we build upon the VDB data structure implemented in the OpenVDB [ 15 ] library. In line with our work, Macenski et al [ 48 ] developed a spatio-temporal voxel system for 3D mapping making use of OpenVDB [ 15 ]. This system encodes sensor observations into an occupancy grid map that additionally implements voxel decay and decay acceleration [ 48 ].…”
Section: Related Workmentioning
confidence: 70%
See 2 more Smart Citations
“…To implement our system, we build upon the VDB data structure implemented in the OpenVDB [ 15 ] library. In line with our work, Macenski et al [ 48 ] developed a spatio-temporal voxel system for 3D mapping making use of OpenVDB [ 15 ]. This system encodes sensor observations into an occupancy grid map that additionally implements voxel decay and decay acceleration [ 48 ].…”
Section: Related Workmentioning
confidence: 70%
“…In line with our work, Macenski et al [ 48 ] developed a spatio-temporal voxel system for 3D mapping making use of OpenVDB [ 15 ]. This system encodes sensor observations into an occupancy grid map that additionally implements voxel decay and decay acceleration [ 48 ]. More recently, Besselmann et al [ 49 ] have also shown promising using the VDB data structure to implement an octree-inspired representation similar to Octomap [ 6 ].…”
Section: Related Workmentioning
confidence: 70%
See 1 more Smart Citation
“…Actualmente, se está trabajando en la implementación en CUDA (Compute Unified Device Architecture en inglés), del algoritmo recientemente presentado: STVL (Macenski, Tsai, & Feinberg, 2020). Se espera correr el mismo a bordo de una Computadora Jetson Nano, la cual integra una GPU embebida.…”
Section: Desarrollounclassified
“…Retail and warehouse spaces can change drastically throughout the year and the state of roadways can be changing by the hour. Much work has been made to address changing environments in robot perception (Macenski, Tsai, et al, 2020), but less has been built in open-source to represent maps of dynamic spaces.…”
mentioning
confidence: 99%